Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas Pada Perusahaan Sub Sektor Perkebunan di BEI - Dwi Putri Ratnasari; Wayan Cipta (Jurnal Akuntansi Profesi, 2021)
This study aims to examine the effect of (1) cash turnover and accounts receivable turnover on profitability, (2) cash turnover on profitability, (3) accounts receivable turnover on profitability in plantation sub-sector companies. The research design used is causal quantitative. The research subjects were plantation sub-sector companies listed on the Indonesia Stock Exchange and the objects were cash turnover, accounts receivable turnover, and profitability. Data were collected by documents recording, and analyzed by multiple linear regression analysis. The results showed that (1) cash turnover and accounts receivable turnover had a significant effect on profitability, (2) cash turnover has a positive and significant effect on profitability, (3) accounts receivable turnover has a positive and significant effect on profitability, this means that overall the size of the company's profitability is influenced by cash turnover and accounts receivable turnover.